2021
DOI: 10.1167/tvst.10.9.23
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Fundus Tessellated Density and Associated Factors in Fundus Images Using Artificial Intelligence

Abstract: Purpose This study aimed to quantitative assess the fundus tessellated density (FTD) and associated factors on the basis of fundus photographs using artificial intelligence. Methods A detailed examination of 3468 individuals was performed. The proposed method for FTD measurements consists of image preprocessing, sample labeling, deep learning segmentation model, and FTD calculation. Fundus tessellation was extracted as region of interest and then the FTD could be obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 28 publications
0
43
0
Order By: Relevance
“…Increasing the number of independent samples, repeating the model's training process and verifying the results may increase the model's accuracy. Furthermore, this large-scale cohort study based on the elderly population gathered detailed eye and whole-body data, including axis length, diopter, weight, and other characteristics that may be linked to FTD ( 16 ). Various research on FT risk variables might be added to this foundation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing the number of independent samples, repeating the model's training process and verifying the results may increase the model's accuracy. Furthermore, this large-scale cohort study based on the elderly population gathered detailed eye and whole-body data, including axis length, diopter, weight, and other characteristics that may be linked to FTD ( 16 ). Various research on FT risk variables might be added to this foundation.…”
Section: Discussionmentioning
confidence: 99%
“…Gender, age, and FTD are employed as major factors in this work to predict FT classification using machine learning methods. Through an artificial intelligence image processing technology, we extracted the exposed choroid from the fundus, and then calculated the average exposed choroidal area per unit fundus area, which is called FTD ( 16 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AI has recently achieved high accuracy in recognizing ocular structure. Deep-learning convolutinal neural networks (CNNs) developed by Li Dong et al (69)(70)(71) have shown superior performance in assessing axial length, subfoveal choroidal thickness, and fundus tessellated density with color fundus photographs. In the diagnosis of multiple ocular disorders, AI outperformed human experts with multimodality imaging, including magnetic resonance imaging (MRI), fundus photographs, and fundus fluorescence angiography (FFA).…”
Section: Discussionmentioning
confidence: 99%
“…The detection of fundus lesions and myopia-related complications in high myopia is an important need, for which deep learning methods such as CNNs already have high accuracy ( Shao et al, 2021 ; Sun et al, 2021 ). Compared to the manual, deep learning methods take only a few hours to a few days in the training phase of the model and can produce instant results when interpreting images.…”
Section: Ai Technology For Myopia Screening and Diagnosismentioning
confidence: 99%